First, multiply each side of the equation by color(red)((2 - 7x^4))(2−7x4) to isolate the zz term while keeping the equation balanced:
15 xx color(red)((2 - 7x^4)) = (10z)/(2 - 7x^4) xx color(red)((2 - 7x^4))15×(2−7x4)=10z2−7x4×(2−7x4)
15color(red)((2 - 7x^4)) = (10z)/color(red)(cancel(color(black)(2 - 7x^4))) xx cancel(color(red)((2 - 7x^4)))
15(2 - 7x^4) = 10z
Now, divide each side of the equation by color(red)(10) to solve for z while keeping the equation balanced:
(15(2 - 7x^4))/color(red)(10) = (10z)/color(red)(10)
((5 xx 3)(2 - 7x^4))/color(red)(5 xx 2) = (color(red)(cancel(color(black)(10)))z)/cancel(color(red)(10))
((color(red)(cancel(color(black)(5))) xx 3)(2 - 7x^4))/color(red)(color(black)(cancel(color(red)(5))) xx 2) = z
(3(2 - 7x^4))/2 = z
z = (3(2 - 7x^4))/2
Or
z = ((3 xx 2) - (3 xx 7x^4))/2
z = (6 - 21x^4)/2
Or
z = 6/2 - (21x^4)/2
z = 3 - (21x^4)/2